Espacialização da população de percevejos pentatomideos no cultivo do arroz irrigado - Pasini, Mauricio Paulo Batistella (2014)
The rice (Oryza sativa L.) is one of the cereals most produced and consumed in the world. In it the insect species, Tibraca limbativentris, Oebalus poecilus and Oebalus ypsilongriseus (Hemiptera: Pentatomidae), generate significant damage. Insect populations in crops can be estimated through the use of interpolation procedures, which can generate continuous surfaces by single point sampling units. The study aimed to compare the methods of ordinary kriging and inverse distance weighted interpolation applied on the spatial distribution of population density T. limbativentris, O. poecilus and O. ypsilongriseus in rice cultivation in Santa Maria, Rio Grande do Sul, Brazil. In the locality of Parada Link, Santa Maria, we generated in six fields, a grid of 30m x 30m. From seeding have been made to seven evaluations for each tillage in area 1m², corresponding to 200 rice plants. In these areas, the adults of the species were quantified and the sum used for the analysis. The values were submitted to the ordinary kriging interpolation in different semivariogram models and inverse distance weighted in different weights being the best for each evaluation compared by cross-validation. The ordinary kriging interpolation method showed better performance than the method of inverse distance weighted applied in the spatial distribution of population density of T. limbativentris and O. poecilus in rice cultivation in Santa Maria, Rio Grande do Sul, Brazil. O. ypsilongriseus could not generate estimates for comparison.